Two New Records of Orchid Species for the Flora of Iraq: Anacamptis papilionacea (L.) R.M. Bateman, Pridgeon & M.W. Chase and Dactylorhiza romana (Sebast.) Soó - Youssef, Sami M.A.; Mahdi, Honar S.; Mergye, Zerevan A.; Salim, Jihad I.; Mahmood, Ahmed M.H.M.; Vela, Errol (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
The Orchidaceae is one of the most cosmopolitan flowering families however, the national floristic knowledge for Iraqi territories is restricted by the outdated and incomplete status of Flora of Iraq. We already recently add two new records of Orchid species for Iraq and the study objective was to pursue the dynamics on field studies and thus provide new contribution for Flora of Iraq. Two new Orchid species were recorded for the first time in Iraq: (i) Anacamptis papilionacea found on Silé waterfall locality (Dostaka mountain, Duhok governorate); and (ii) Dactylorhiza romana found in Hariké locality (Gara mountain, Duhok governorate). Field illustrations, infraspecific identification (A. papilionacea subsp. schirwanica; D. romana subsp. georgica), environment and geographical distribution, conservation status and a brief discussion about the new records are provided. This study highlights the importance of floristic surveys and their continuity over time as a first step towards the modern floristic knowledge including open databases.